2023
DOI: 10.1021/jacs.3c06164
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomers Self-Sort into Separate Counter-Twisted Ribbons of the Fddd Liquid Crystal─Antiferrochirality and Parachirality

Yan Wang,
Ya-Xin Li,
Liliana Cseh
et al.

Abstract: The recently discovered orthorhombic liquid crystal (LC) phase of symmetry Fddd is proving to be widespread. In this work, a chiral hydroxybutyrate linkage is inserted into the molecular core of hexacatenar rodlike compounds, containing a thienylfluorenone fluorophore. In addition to more usual tools, the methods used include grazing-incidence X-ray scattering, modulated differential scanning calorimetry (DSC), flash DSC with rates up to 6000 K/s, and chiro-optical spectroscopies using Mueller matrix method, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This phase consists of adjacent right- and left-handed helical columns containing separated pure chiral enantiomers. While the racemic high-temperature columnar phase forms from the melt within 20 ms, the local deracemization and formation of the Fddd phase take 20 s . In this case, the rate-determining step is unpairing, while in the PLA case, it is pairing.…”
Section: Discussionmentioning
confidence: 99%
“…This phase consists of adjacent right- and left-handed helical columns containing separated pure chiral enantiomers. While the racemic high-temperature columnar phase forms from the melt within 20 ms, the local deracemization and formation of the Fddd phase take 20 s . In this case, the rate-determining step is unpairing, while in the PLA case, it is pairing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the precise chiral recognition in biomolecules, controlled chiral communication and expression are essential in many self-assembled systems, such as self-assembled small molecules, [6] helical polymers, [7] supramolecular polymers, [8] and liquid crystals (LCs). [9][10][11] Meanwhile, dynamic control of chiral structures is important for the development of functional chiroptical materials, which are essential for the specific functions. [12][13][14][15] This also enables it to show promising applications in the fields of chiral recognition, asymmetric catalysis, chiral modulation, enantiomeric sensors, and LC materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the precise construction and artificially controllable regulation of chiral structures would be expected to enable dynamic control of the corresponding biological functions. Similar to the precise chiral recognition in biomolecules, controlled chiral communication and expression are essential in many self‐assembled systems, such as self‐assembled small molecules, [6] helical polymers, [7] supramolecular polymers, [8] and liquid crystals (LCs) [9–11] . Meanwhile, dynamic control of chiral structures is important for the development of functional chiroptical materials, which are essential for the specific functions [12–15] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently we found that similar chiral compounds bearing six chains form a LC phase of coexisting straight right-and left-handed helical columns, spacegroup Fddd. [26] However, the Fddd formed only if both R and S enantiomers were present and not in pure enantiomers. Thus a similar situation may be expected in the gyroid cubic, with its coexisting right and left-handed networks, since in a pure enantiomer 50 % of molecules would have to enter the network of "wrong" chirality.…”
mentioning
confidence: 99%
“…With two or more end-chains these so-called polycatenars may form either a network-based LC phase with 3D long-range order [13][14][15][16][17][18][19] or a columnar phase with 2D [20][21][22][23] and sometimes 3D order. [24][25][26] The 3D network phases are formed of 2 [2,12] or 3 [27,28] infinite interpenetrating nets-see Figure 1. The network segments are columns made up of stacked "rafts", each containing 2-4 molecules lying side-by-side perpendicular to the column axis (Figure 1c).…”
mentioning
confidence: 99%